Spontaneous Cerebrospinal Fluid Leak through the Posterior Aspect of the Petrous Bone - Nadaraja, Garani S.; Monfared, Ashkan; Jackler, Robert K. (Journal of Neurological Surgery Part B: Skull Base, 2012)
Spontaneous cerebrospinal fluid (CSF) leak through the posterior fossa (PF) aspect of the petrous bone is exceedingly rare. A case series allows analysis of etiologies and how they may differ from the more common middle fossa (MF) route of leakage. The design was a retrospective case series. The setting was a tertiary care institution. A series of three patients with PF spontaneous CSF leaks was identified. High-resolution imaging (CT and MRI) and intraoperative observations were evaluated. Both in this series and in previously reported cases, patients share the demographics typically found in the MF leak population. In our series, two patterns of PF CSF leak were identified: (1) large unilateral with cerebellar encephalocele and (2) small punctate defects just lateral to the endolymphatic sac. Two presented with simultaneous MF and PF leaks suggesting a shared etiology, at least in some cases, with a role for increased intracranial pressure. In spontaneous CSF leaks, it is important to evaluate the posterior petrous bone along with the tegmen. The concomitant appearance of MF with PF leaks points out the risk that repair via MF craniotomy could fail to identify a leakage site in the vicinity of the endolymphatic sac.
Keywords: cerebrospinal fluid leak; arachnoid granulation; petrous bone; posterior fossa